The role of oxidative stress in the formation of postmenopausal osteoporosis - I S Zakharov; G I Kolpinskiy; G A Ushakova; G V Wavin (IP Berlin A.V., 2014)
In the present review discusses the impact of oxidative stress on bone metabolism. Shows the importance of pro-oxidants in the physiology and pathology of bone remodelling. Key role oxidative stress begins to play in post-menopausal. This is due to a decrease in estrogen levels and the formation of involutional changes in the body, including bone metabolism. Furthermore, the article addresses the issues of antioxidant protection involved in maintaining bone homeostasis.